How to build an aircraft carrier the incredible story of the men and women who brought Britain's biggest warship to life - Terrill, Chris (Michael Joseph, 2022)
65,000 tons. 280 metres long. A flight deck the size of 60 tennis courts. A giant piece of sovereign British territory that's home to up to 50 aircraft. HMS Queen Elizabeth is the biggest ship in Royal Navy's history and one of the most ambitious and exacting engineering projects ever undertaken in the UK. But it's her ship's company of 700, alongside an aviation wing of 900 air and ground crew, that is Big Lizzie's beating heart. And How To Build An Aircraft Carrier tells their story. From before the first steel of her hull was cut, Christ Terrill has enjozed unprecedented access to the Queen Elizabeth and the men and women who have brought her to life. From Jerry Kyd, the ship's inspirational captain, to Cdr Nathan Gray, the first pilot to land Britain's new stealth jet fighter on her deck, Terrill has won the trust and confidence of the ship's people. How To Build An Aicraft Carrier tells the story of Britain at her best: innovative, confident, outward-looking and world-beating.